Triumph of the city : how our greatest invention makes us richer, smarter, greener, healthier, and happier - Glaeser, Edward L. (Edward Ludwig), 1967- (New York : Penguin Press, 2011)
A pioneering urban economist offers fascinating, even inspiring proof that the city is humanity's greatest invention and our best hope for the future.
Our urban species -- What do they make in Bangalore? -- Why do cities decline? -- What's good about slums? -- How were the tenements tamed? -- Is London a luxury resort? -- What's so great about skyscrapers? -- Why has sprawl spread? -- Is there anything greener than blacktop? -- How do cities succeed? -- Flat world, tall city.
Includes bibliographical references (p. [307]-323) and index.
Keywords: Urbanization; Cities and towns -- Growth; Urban economics; Sociology, Urban